PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SIMAR JAYA - Revaldo Timothy Edwardo Simanjuntak; Herold Moody Manalu (Jurnal Ekonomis, 2022)
The purpose of this study was to examine and determine the work environment and work discipline on employee performance. The type of research used is quantitative. This research was conducted at PT. Simar Jaya with a population of 30 employees. Data processing and analysis techniques used validity and reliability tests, descriptive statistical tests, classical assumption tests, multiple linear regression tests, T and F hypothesis tests, and coefficients of determination tests. The results of the study stated that the work environment and work discipline had an effect on employee performance at PT. Simar Jaya. Environmental comfort and a high level of discipline will affect employee performance